2012
DOI: 10.1016/j.rmcr.2012.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Sweet's syndrome with pulmonary involvement: Case report and literature review

Abstract: A 74 year old female presented with fever, associated with papules and plaque in her upper and lower extremities. Exams revealed blood leukocytosis and a positive urine culture. Antibiotic therapy was initiated with no clinical response. After 1 week, chest X-ray showed right upper lobe alveolar infiltrate. A skin biopsy of the lesion showed infiltration by neutrophils, consistent with Sweet's Syndrome. Patient's condition progressively worsened, requiring oxygentherapy. Bronchoscopy and bronchoalveolar lavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Chest X-ray usually shows diffuse pulmonary infiltrates, and unilateral or bilateral interstitial infiltrates can be confirmed on chest CT. In some cases, pulmonary opacities and pleural effusions have also been described 6 7. The majority of cases show prompt improvement following oral or intravenous corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chest X-ray usually shows diffuse pulmonary infiltrates, and unilateral or bilateral interstitial infiltrates can be confirmed on chest CT. In some cases, pulmonary opacities and pleural effusions have also been described 6 7. The majority of cases show prompt improvement following oral or intravenous corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary involvement in Sweet’s syndrome manifests as a neutrophilic alveolitis with corticosteroid-responsive culture-negative pulmonary infiltrates 6. A recent review article identified 34 previously reported cases of Sweet’s syndrome with pulmonary involvement 7. Cutaneous and pulmonary symptoms are usually concomitant, although occasionally skin lesions can precede lung involvement by months or years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweet's rash preceded lung symptoms in 6 cases, while the other 5 of 11 patients complained of the respiratory condition first. Imaging work most frequently revealed interstitial lung opacities that can be unilateral [6072] or bilateral [73–84] with or without pleural effusions and no site or lobe predilection [78, 85, 86]. A presenting scenario such as this can be easily confused with pneumonia especially when a biopsy from the lesions is not feasible in critically ill patients, those prone to bleeding or other high risk complications [72, 87].…”
Section: Neutrophilic Dermatosesmentioning
confidence: 99%
“…Sweet Syndrome (SS; also known as acute febrile neutrophilic dermatosis) is a systemic inflammatory disorder that is typically characterized by high fever, leukocytosis, and tender regions of erythema. 2 Although it carries a link to MDS, malignancy-associated SS is most often associated with acute myelogenous leukemia (AML), with a temporal pattern revolving around the onset and relapse of underlying disease. 3,4 In some cases of MDS, a transformation to acute leukemia can take place.…”
Section: Introductionmentioning
confidence: 99%